THE HUBUNGAN ANTARA LAMA DUDUK DENGAN SINDROMA PIRIFORMIS PADA PEMAIN GAME ONLINE DI GAME CENTER GO-KOOL DENPASAR - Mediastama, I Gd; Silakarma, Dedi; Griadhi, Adiarta (Majalah Ilmiah Fisioterapi Indonesia; Vol 3 No 2 (2015): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2015.v03.i02.p03)
This research aims to know the relationship long sitting with piriformis syndrome on online game players at game center Go-Kool Denpasar. Design research is a cross-sectional study conducted in May and June 2014, with a population of online game players in game center Go-Kool Denpasar that meet the criteria for inclusion and exclusion. From a number of online game players selected by simple random sampling, and obtained the 50 samples. The results showed that out of the 50 players online gaming brings 36 people respondents who sat with duration more than 4 hours (66,7%) of 24 people were experiencing symptoms of piriformis syndrome and 12 people (33,3%) were the other do not experience symptoms of piriformis syndrome, while the 14 respondents who play games online with a duration of less than 4 hours sitting 4 people (28,6%) of whom had symptoms of piriformis syndrome and 10 people (71,4%) did not experience symptoms of piriformis syndrome. Based on chi-square test p value = 0.015 (p<0.05), which means there is a significant association between long sitting with piriformis syndrome.
Keywords: Long Sitting, Piriformis Syndrome, Online Game Players